Supervisi Kepala Ruangan dalam Menigkatkan Budaya Keselamatan Pasien - Siti Fatonah; Tito Yustiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the correlation between the supervision of the head of the room with the culture of patient safety in the Nganjuk Hospital inpatient installation. This research method is a quantitative analytic study with a cross-sectional study design. The results showed that most respondents consisted of women (74.4%) aged between 26 - 35 years (52.6%) who had a D3 / equivalent education (71.8%). The results of the bivariate analysis showed that the p-value was 0.000 <0.05. In conclusion, there is a significant relationship between the supervision of the head of the room with the culture of patient safety in the Inpatient Installation of Nganjuk Hospital. Keywords: Patient Safety Culture, Hospital, Supervision